A Study on Temperature Control System For Biomass Gasification Process - Wan Mohd Huzaifi, W Ibrahim (2012)
The thermal chemical conversion process is used to change the biomass to the renewable energy source. The process is distinguished by different temperature. The main goal of this study was experimentally about the ability of the direct fired furnace in control the temperature of furnace and reactor. This studied by do the modification on the system to regulate and control the fuel input in order to know the required energy for the direct fired system. The minimum setting fuel flow rate is 18 L/min that produce 28.2KW energy. By limitation of flow meter, the maximum fuel flow rate was 22L/min that produced 34.47 KW of energy. But the setting of opening air damper is gave the effect the furnace and reactor temperature. The fuel flow rate constant at 22L/min but the opening air damper setting is changed to get the required temperature for desired process. 3.6 of opening air damper setting are used for torrefaction process and 0.6 is for pyrolysis process. For gasification process could not achieve because to many heat loss occur in this system. Based on the energy produced, the theoretical reactor temperature is calculated based on heat transfer equation for hollow cylinder. The comparison between theoretical and actual reactor temperature showed there is 13% of heat loss occurred.